Frequent polymorphic changes but not mutations of TRAIL receptors DR4 and DR5 in mantle cell lymphoma and other B-cell lymphoid neoplasms - V Fernandez; P Jares; S Bea; I Salaverria; E Guino; S de Sanjose; D Colomer; G Ott; E Montserrat; E Campo (Haematologica, 2004)
BACKGROUND AND OBJECTIVES: Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) receptors DR4 and DR5 have been mapped to chromosome 8p21-22, a region frequently deleted in different lymphoid neoplasms. DESIGN AND METHODS: To investigate the potential alterations of these genes in lymphoid neoplasms, we examined the presence of gene mutations in exons 3, 4, and 9 in 69 cases with mantle cell lymphoma (MCL), 16 with chronic lymphocytic leukemia (CLL), 12 with follicular lymphomas (FL) and 17 with large B-cell-lymphomas (DLBCL), as well as in 4 lymphoid cell lines carrying the t(11;14) translocation, and 91 healthy blood donors. RESULTS: Three CLL and three MCL cases had 8p deletions. Two nucleotide changes in or near the intron 3 splice consensus sequence and a silent change were found. These rare changes were also present in the germ-line of the patients. The DR4 death domain A1322G polymorphism was significantly more frequent in MCL [odds ratio (OR) = 5.9; 95% confidence interval (CI), 1.92-18.1] and CLL (OR = 4.5; CI, 1.18-17) patients than in a sex and age-adjusted healthy population. In contrast, the DR4 exon 4 C626G polymorphism was associated with a significant overall decreased risk for MCL (OR = 0.3; CI, 0.12-0.8). No mutations or cancer-associated polymorphic changes were found in DR5 domains. INTERPRETATION AND CONCLUSIONS: These findings indicate that mutations of DR4 and DR5 are uncommon in lymphoid neoplasms but DR4 polymorphic alleles may contribute to the pathogenesis of these malignancies.